Nanosized titanium dioxide elevates toxicity of cationic metals species for Daphnia – have aging and natural organic matter an unexpected impact?. Issue 1 (2nd January 2022) - Roy, Rajdeep; Kandrapu, Vinod Kumar; Kempter, Lucas; Islam, Rezaul; Kalčíková, Gabriela; Schulz, Ralf; Bundschuh, Mirco
Abstract: In aquatic ecosystems, nanosized titanium dioxide particles (nTiO2 ) likely interact with natural organic matter (NOM) and may alter the ecotoxicity of co-occurring metals. The magnitude of changes in toxicity may be modulated by the duration of interactions (i.e. aging) between these factors. As those interactions are hardly addressed in literature, the present study aimed at assessing the impact of aging durations (0, 1, 3 and 6 days) on metals with mainly cationic (silver (Ag), cadmium (Cd)) or anionic (arsenic (As)) toxic ions in combination with three nTiO2 levels (0.0, 0.6 and 3.0 mg/L) and two NOM levels (0 versus 8 mg TOC/L). The interaction of these factors was additionally investigated for two aging scenarios: in one scenario nTiO2 were aged together with one of the metals, while in other scenario metals were added to aged nTiO2 . Subsequently, their combined acute effects on Daphnia magna were assessed. The results uncovered that nTiO2 elevate the toxicity of metals with mainly cationic species (i.e. Ag + and Cd 2+ ) with the effect size depending on their valence electron. Contrary, nTiO2 have no impact on the metal with mainly anionic species (i.e. HAsO4 2− ). Furthermore, NOM reduced metal toxicity only for Ag and aging duration had a limited impact on the test outcome suggesting that relevant interactions between metal and nTiO2 occur rather quick (below 24 h). These findings suggest that the charge of metals' most toxic species is the determining factor for its interaction with nanoparticles and the resulting ecotoxicological effect assessment.